Electronic-grade quartz glass fiber cloth and preparation method thereof

By precision controlling the preparation process of quartz fiberglass cloth, including melting, precision filtration and homogenization of high-purity quartz sand, drawing fibers and applying wetting agents, the problem of insufficient purity and uniformity of fiberglass cloth in traditional methods is solved, and the preparation of high-performance electronic grade quartz fiberglass cloth is realized.

CN119800695AInactive Publication Date: 2025-04-11ZHONGYI (TAIXING) ENVIRONMENTAL PROTECTION TECH CO LTD

Patent Information

Application Number
CN202510300216.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-14
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional quartz fiberglass fabric preparation methods cannot fully ensure high purity and uniformity, resulting in limited electronic-grade application performance.

Method used

High-purity quartz sand is used to melt in an arc furnace, and after precision filtration and homogenization, quartz glass fiber is drawn using a platinum-rhodium alloy leakage plate, and a special wetting agent is uniformly coated on the fiber surface, followed by high-temperature sintering and electron beam irradiation.

Benefits of technology

It improves the purity and uniformity of quartz fiberglass cloth, improves its electrical properties and cleanliness, and is suitable for high-performance electronic applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800695A_ABST
    Figure CN119800695A_ABST
Patent Text Reader

Abstract

The invention provides electronic-grade quartz glass fiber cloth and a preparation method thereof. The method comprises the following steps: selecting high-purity quartz sand, melting at high temperature, precisely filtering, and homogenizing; preparing a special impregnating compound; drawing fibers through a platinum-rhodium alloy bushing and coating the fibers with an impregnating compound; weaving into a cloth blank; performing high-temperature sintering treatment; the electrical property is improved through electron beam irradiation treatment; and cleaning with ultrapure water and drying to ensure the electronic grade cleanliness. According to the invention, high purity, uniformity and excellent electrical properties of the electronic-grade quartz glass fiber cloth can be ensured, and the requirements of the electronic industry on high-performance materials are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of insulating material preparation, and more specifically, to an electronic grade quartz glass fiber cloth and a preparation method thereof. Background Art

[0002] Electronic grade quartz glass fiber cloth is widely used in the electronics industry due to its excellent electrical insulation, high temperature resistance and chemical stability, especially in the fields of semiconductor manufacturing, integrated circuit packaging, and electronic insulation materials. Traditional preparation methods often cannot fully guarantee the high purity and uniformity of quartz glass fiber cloth, resulting in limited performance in electronic grade applications. These methods have problems with imprecise control during melting, filtration, homogenization, and selection and coating of impregnants, making it difficult for the final product to meet the strict requirements of the electronics industry for material purity and performance stability. In addition, traditional sintering and irradiation processing techniques may not be able to effectively remove impurities and by-products on the surface of the material, thereby affecting the cleanliness and electrical properties of the product.

[0003] According to a glass cloth disclosed (publication number: JP2024-150218A), the inventors found that there are at least the following problems or defects: the preparation process of the quartz glass fiber cloth lacks fine control over the purity of the raw materials and the preparation conditions, resulting in insufficient product purity; the filtration and homogenization treatments are not fine enough, resulting in the presence of unmelted particles and impurities in the fiber cloth; the preparation and coating technology of the impregnating agent is not mature enough, affecting the surface quality and electrical properties of the fiber cloth; the sintering and irradiation treatment technology is not advanced enough to effectively improve the cleanliness and electrical properties of the fiber cloth. Summary of the invention

[0004] The invention provides an electronic grade quartz glass fiber cloth and a preparation method thereof.

[0005] In a first aspect of the present invention, a method for preparing electronic grade quartz glass fiber cloth is provided, comprising the following steps: S1: Select high-purity quartz sand, put it into an arc furnace, melt it at a high temperature of 2800℃-3000℃, and obtain uniform quartz glass liquid for standby use; S2: Precision filter the molten quartz glass liquid using a ceramic filter with a pore size of 0.1-0.5μm to remove impurities and unmelted particles to ensure the high purity of the glass liquid; S3: homogenizing the filtered quartz glass liquid, placing the glass liquid in a rotating stirring device, and stirring at a speed of 50-100 rpm for 30-60 minutes to ensure the uniformity of the glass liquid composition and temperature; S4: prepare special infiltrant; S5: The quartz glass liquid in step S3 is passed through a platinum-rhodium alloy leak plate to be drawn into a quartz glass fiber with a diameter of 3-9 μm at a specific flow rate and speed, and at the same time, the special impregnating agent in step S4 is evenly coated on the surface of the just-drawn fiber; S6: Bundling the quartz glass fibers coated with the sizing agent, winding, arranging, twisting the raw fibers, and weaving them into electronic grade quartz glass fiber cloth embryos with specific warp and weft densities through a weaving device; S7: performing high-temperature sintering treatment on the fiber cloth embryo to remove excess impregnating agent residue to obtain electronic grade quartz glass fiber cloth; S8: subjecting the electronic grade quartz glass fiber cloth sintered at high temperature to electron beam irradiation treatment, with an irradiation dose of 10-20 kGy, to improve the electrical properties of the fiber cloth; S9: The fiber cloth treated with electron beam irradiation is cleaned with ultrapure water, treated with coupling agent and dried in a clean environment to ensure that it meets the cleanliness requirements of electronic grade.

[0006] Furthermore, the step S4 comprises the following steps: S41: dissolving a silane coupling agent, a lubricant, and an antistatic agent in deionized water according to a mass ratio to prepare a basic solution; S42: Add nano-sized titanium dioxide particles to the base solution, and ultrasonically disperse the solution in an ultrasonic dispersion device for 30-60 minutes to evenly disperse the nano-particles to prepare a special wetting agent.

[0007] Furthermore, in step S5, the coating amount of the special sizing agent is 0.5%-1.5% of the mass of the quartz glass fiber.

[0008] Furthermore, the aperture accuracy of the platinum-rhodium alloy leak plate is controlled within ±0.05 μm.

[0009] Furthermore, the speed of drawing the quartz glass fiber is 1000-1500 m / min.

[0010] Further, in step S41, the mass fraction of the silane coupling agent in the base solution is 13%-15%, the mass fraction of the lubricant in the base solution is 2%-7%, the mass fraction of the antistatic agent in the base solution is 2%-7%, and the mass fraction of deionized water in the base solution is 71%-83%.

[0011] Furthermore, in step S42, the particle size of the nano-scale titanium dioxide particles is 20-50 nm.

[0012] Furthermore, the mass fraction of the nano-scale titanium dioxide particles in the special wetting agent is 3%-8%.

[0013] Furthermore, the temperature of the high temperature sintering treatment is 800°C-1000°C, and the treatment time is 30-60 minutes.

[0014] In a second aspect of the present invention, there is provided an electronic grade quartz glass fiber cloth, which is prepared by the preparation method of the electronic grade quartz glass fiber cloth, comprising: The fiber structure is formed by weaving quartz glass fibers with a diameter of 3-9μm. The quartz glass fibers are first bundled, then wound, arranged, and twisted, and finally woven into a cloth-like structure with a specific warp and weft density ranging from 30×30 strands / cm² to 40×40 strands / cm². Wetting agent coating: A special wetting agent is coated on the fiber structure surface of the electronic grade quartz glass fiber cloth. The special wetting agent consists of a basic solution and nano-scale titanium dioxide particles. The basic solution is prepared by dissolving silane coupling agent, lubricant and antistatic agent in deionized water according to the mass ratio. The mass fraction of silane coupling agent in the basic solution is 13% - 15%, the mass fraction of lubricant in the basic solution is 2% - 7%, the mass fraction of antistatic agent in the basic solution is 2% - 7%, the mass fraction of deionized water in the basic solution is 71% - 83%, the particle size of nano-scale titanium dioxide particles is 20 - 50nm, and the mass fraction in the special wetting agent is 3% - 8%, and the nano-scale titanium dioxide particles are uniformly dispersed in the basic solution by ultrasonic dispersion for 30 - 60min. The coating amount of the special wetting agent is 0.5% - 1.5% of the mass of the quartz glass fiber.

[0015] According to the above-mentioned embodiments of the present invention, at least the following beneficial effects are achieved: the method for preparing electronic-grade quartz glass fiber cloth provided by the present invention can improve the purity and uniformity of the product. By melting high-purity quartz sand at high temperature and using precision filtration and homogenization treatment to effectively remove impurities and unmelted particles, the high purity and uniformity of the composition of the quartz glass liquid can be ensured. In addition, a special impregnating agent is used to evenly coat the fiber surface, and after high-temperature sintering and electron beam irradiation treatment, not only the electrical properties of the fiber cloth can be improved, but also it can be ensured that it meets the requirements of electronic-grade cleanliness. The quartz glass fiber cloth prepared by this method has better electrical insulation and chemical stability, and is suitable for high-performance electronic applications.

[0016] The preparation method of the present invention can also effectively control the diameter of the fiber and the warp and weft density of the cloth, so that the electronic grade quartz glass fiber cloth has more consistent and uniform physical properties. By accurately controlling the drawing speed and the coating amount of the impregnant, and optimizing the conditions of sintering and irradiation treatment, the mechanical strength and electrical properties of the fiber cloth can be further improved. These improvements make the fiber cloth more widely used in the electronics industry, especially in the extremely demanding fields of semiconductor manufacturing and integrated circuit packaging, and can provide more reliable and stable insulation protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The above and other objects, features and advantages of the exemplary embodiments of the present invention will become readily understood by reading the detailed description below with reference to the accompanying drawings. In the accompanying drawings, several embodiments of the present invention are shown in an exemplary and non-limiting manner, in which: Figure 1 A schematic flow chart of a method for preparing electronic grade quartz glass fiber cloth provided in one embodiment of the present invention. DETAILED DESCRIPTION

[0018] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0019] The present invention provides a method for preparing electronic grade quartz glass fiber cloth, comprising the following steps: Figure 1 shown.

[0020] S1: Select high-purity quartz sand, put it into an arc furnace, melt it at a high temperature of 2800℃-3000℃, and obtain uniform quartz glass liquid for standby use; S2: Precision filter the molten quartz glass liquid using a ceramic filter with a pore size of 0.1-0.5μm to remove impurities and unmelted particles to ensure the high purity of the glass liquid; S3: homogenizing the filtered quartz glass liquid, placing the glass liquid in a rotating stirring device, and stirring at a speed of 50-100 rpm for 30-60 minutes to ensure the uniformity of the glass liquid composition and temperature; S4: prepare special infiltrant; S5: The quartz glass liquid in step S3 is passed through a platinum-rhodium alloy leak plate to be drawn into a quartz glass fiber with a diameter of 3-9 μm at a specific flow rate and speed, and at the same time, the special impregnating agent in step S4 is evenly coated on the surface of the just-drawn fiber; S6: Bundling the quartz glass fibers coated with the sizing agent, winding, arranging, twisting the raw fibers, and weaving them into electronic grade quartz glass fiber cloth embryos with specific warp and weft densities through a weaving device; S7: performing high-temperature sintering treatment on the fiber cloth embryo to remove excess impregnating agent residue to obtain electronic grade quartz glass fiber cloth; S8: subjecting the electronic grade quartz glass fiber cloth sintered at high temperature to electron beam irradiation treatment, with an irradiation dose of 10-20 kGy, to improve the electrical properties of the fiber cloth; S9: The fiber cloth treated with electron beam irradiation is cleaned with ultrapure water to remove surface impurities and possible by-products. After being treated with a coupling agent, it is dried in a clean environment to ensure that it meets the electronic grade cleanliness requirements.

[0021] Specifically, in step S1, high-purity quartz sand is selected, and its purity requirement is 99.999% or more. The quartz sand here can be obtained from natural quartz ore after multiple purification treatments. The purification method can be a combination of physical and chemical methods, such as first removing most of the impurities by flotation, and then further removing metal impurities by acid leaching. The purified quartz sand is put into an electric arc furnace and melted at a high temperature of 2800℃-3000℃ to obtain a uniform quartz glass liquid for standby use. In this process, the electrode material of the electric arc furnace uses high-quality graphite electrodes to ensure the stability and uniformity of the high-temperature environment, and the temperature control accuracy of the furnace is ±10℃, thereby ensuring the reliability of the melting process.

[0022] Specifically, in step S2, a ceramic filter with a pore size of 0.1-0.5 μm is used to precisely filter the molten quartz glass liquid to remove impurities and unmelted particles. The ceramic material of the ceramic filter is selected from alumina ceramics with high chemical stability, and its pore structure is uniform, which can effectively intercept impurities and unmelted particles with a particle size larger than the set pore size to ensure the high purity of the glass liquid. During the filtration process, the filtration pressure is maintained at 0.2-0.5 MPa to ensure the efficiency and effect of the filtration while avoiding adverse effects on the performance of the glass liquid.

[0023] Specifically, in step S3, the filtered quartz glass liquid is placed in a rotating stirring device, the stirring paddle of which is made of stainless steel and has good high temperature resistance and corrosion resistance. Stir at a speed of 50-100 rpm for 30-60 minutes to ensure the uniformity of the glass liquid composition and temperature. During the stirring process, the temperature and composition uniformity of the glass liquid are monitored in real time by a temperature sensor and a composition analyzer. When the temperature fluctuation exceeds ±5°C or the composition deviation exceeds the set threshold, the stirring speed and time are adjusted to achieve the best homogenization effect.

[0024] Specifically, step S4 includes the following steps: S41: dissolving a silane coupling agent, a lubricant, and an antistatic agent in deionized water according to a mass ratio to prepare a basic solution; S42: adding nano-scale titanium dioxide particles to the basic solution, and ultrasonically dispersing the solution in an ultrasonic dispersion device for 30-60 minutes to uniformly disperse the nanoparticles to obtain a special wetting agent.

[0025] Specifically, in step S41, a silane coupling agent, a lubricant, and an antistatic agent are dissolved in deionized water according to a mass ratio to prepare a basic solution, wherein the mass fraction of the silane coupling agent in the basic solution is 13%-15%, the mass fraction of the lubricant in the basic solution is 2%-7%, the mass fraction of the antistatic agent in the basic solution is 2%-7%, and the mass fraction of deionized water in the basic solution is 71%-83%. The silane coupling agent may be γ-aminopropyltriethoxysilane, which can enhance the chemical bonding between the quartz glass fiber and the impregnating agent and improve the strength and toughness of the fiber; the lubricant may be polytetrafluoroethylene powder, which has good lubrication properties and can reduce the friction coefficient between fibers; the antistatic agent may be a quaternary ammonium salt compound, which can effectively prevent static electricity accumulation. In step S42, the particle size of the added nano-scale titanium dioxide particles is 20-50 nm, the power of the ultrasonic dispersion equipment is 800 W, and the frequency is 40 kHz. During the ultrasonic dispersion process, the nano-scale titanium dioxide particles are evenly dispersed in the base solution to form a special impregnation agent. The nano-scale titanium dioxide particles can improve the anti-ultraviolet performance of the fiber cloth, and can also improve the wear resistance and chemical corrosion resistance of the fiber cloth.

[0026] Specifically, in step S5, the quartz glass liquid in step S3 is passed through a platinum-rhodium alloy leak plate, the aperture accuracy of the platinum-rhodium alloy leak plate is controlled at ±0.05μm, and the leak plate is manufactured using advanced micromachining technology to ensure the consistency and accuracy of its aperture. The quartz glass fiber with a diameter of 3-9μm is drawn at a speed of 1000-1500m / min and a flow rate of 0.8-1.2mL / min. At the same time, the special impregnating agent in step S4 is evenly coated on the surface of the fiber just drawn by a belt coater, and the coating amount of the special impregnating agent is 0.5%-1.5% of the mass of the quartz glass fiber. During the coating process, the spraying amount of the impregnating agent is controlled by a high-precision flow controller to ensure the uniformity of the coating.

[0027] Specifically, in step S6, the quartz glass fibers coated with the sizing agent are bundled and passed through a weaving device, which uses a computer control system to accurately control the arrangement of the warp and weft lines, to weave into electronic grade quartz glass fiber cloth embryos with specific warp and weft densities (e.g., 30×30 strands / cm²-40×40 strands / cm²). During the weaving process, the tension of the fiber is monitored in real time by a tension sensor. When the tension exceeds the set range, the weaving speed and the fiber feeding speed are automatically adjusted to ensure the uniformity of the weaving and the quality of the cloth embryos.

[0028] Specifically, in step S7, the fiber cloth embryo is subjected to high-temperature sintering treatment at a high temperature of 800°C-1000°C for 30-60 minutes. The high-temperature sintering furnace used has a zoned heating function, which can realize temperature gradient control to ensure that the fiber cloth embryo is heated evenly during the sintering process. At the same time, the atmosphere in the sintering furnace can be controlled to an inert gas (such as argon) environment to prevent the fiber cloth embryo from being oxidized at high temperatures. Through this high-temperature sintering treatment, the excess impregnating agent residue is removed to obtain an electronic grade quartz glass fiber cloth.

[0029] Specifically, in step S8, the electronic grade quartz glass fiber cloth after high temperature sintering is subjected to electron beam irradiation treatment, and a high energy electron beam accelerator is used for irradiation, wherein the electron beam energy is 1-3 MeV, and the irradiation dose is 10-20 kGy, so as to improve the electrical properties of the fiber cloth. The irradiation process is carried out in a vacuum environment to reduce the interference of impurities in the air on the irradiation effect, and at the same time, the oxidation of the fiber cloth can be avoided. Electron beam irradiation treatment can change the molecular structure inside the fiber cloth, improve its dielectric constant and insulation resistance, and make it more suitable for electronic grade applications. Specifically, in step S9, the fiber cloth after electron beam irradiation treatment is cleaned with ultrapure water, the resistivity of ultrapure water is 18.2 MΩ·cm, and the cleaning is carried out in an ultrasonic cleaning tank, the ultrasonic frequency is 60 kHz, and the cleaning time is 10-20 min to remove surface impurities and possible by-products. The cleaned fiber cloth is then dried in a clean environment with a cleanliness level of ISO4, using low-humidity nitrogen blowing to avoid the introduction of impurities and moisture, ensuring that it meets the electronic-grade cleanliness requirements. The electronic-grade quartz glass fiber cloth prepared by the above-mentioned electronic-grade quartz glass fiber cloth preparation method includes components such as quartz glass fiber and a sizing agent, and the proportion of the components will be adjusted according to the specific preparation process.

[0030] The present invention also provides an electronic grade quartz glass fiber cloth, comprising: The fiber structure is formed by weaving quartz glass fibers with a diameter of 3-9μm. The quartz glass fibers are first bundled, then wound, arranged, and twisted, and finally woven into a cloth-like structure with a specific warp and weft density ranging from 30×30 strands / cm² to 40×40 strands / cm². Wetting agent coating: A special wetting agent is coated on the fiber structure surface of the electronic grade quartz glass fiber cloth. The special wetting agent consists of a basic solution and nano-scale titanium dioxide particles. The basic solution is prepared by dissolving silane coupling agent, lubricant and antistatic agent in deionized water according to the mass ratio. The mass fraction of silane coupling agent in the basic solution is 13% - 15%, the mass fraction of lubricant in the basic solution is 2% - 7%, the mass fraction of antistatic agent in the basic solution is 2% - 7%, the mass fraction of deionized water in the basic solution is 71% - 83%, the particle size of nano-scale titanium dioxide particles is 20 - 50nm, and the mass fraction in the special wetting agent is 3% - 8%, and the nano-scale titanium dioxide particles are uniformly dispersed in the basic solution by ultrasonic dispersion for 30 - 60min. The coating amount of the special wetting agent is 0.5% - 1.5% of the mass of the quartz glass fiber.

[0031] The fiber diameter is 3-9μm, which is determined after comprehensive consideration of the performance requirements of electronic grade applications for fiber cloth such as electrical insulation, flexibility and mechanical strength. For example, in semiconductor manufacturing, the appropriate fiber diameter helps improve the insulation performance of circuit boards and the stability of signal transmission.

[0032] Quartz glass fiber needs to be bundled, wound, arranged, and twisted before being woven into a cloth-like structure with a specific warp and weft density (30×30 strands / cm² - 40×40 strands / cm²). These processing steps can enhance the bonding force between fibers and improve the overall performance of the fiber cloth. The specific warp and weft density not only ensures the strength of the fiber cloth, but also meets the requirements of electronic-grade applications for light, thin, and uniform materials. For example, in integrated circuit packaging, it can achieve good coverage and protection without affecting the heat dissipation and signal transmission of electronic components.

[0033] The basic solution of the special sizing agent is prepared by silane coupling agent, lubricant, antistatic agent and deionized water in a specific mass ratio. The mass fraction of silane coupling agent is 13% - 15%, which can enhance the chemical bonding between quartz glass fiber and sizing agent, and improve the strength and toughness of fiber; the mass fraction of lubricant is 2% - 7%, which can reduce the friction coefficient between fibers and prevent fiber damage during processing and use; the mass fraction of antistatic agent is 2% - 7%, which can effectively prevent static electricity accumulation and avoid static electricity interference and damage to electronic components; deionized water is used as a solvent, with a mass fraction of 71% - 83%, to ensure that all components are evenly dispersed.

[0034] The mass fraction of nano-sized titanium dioxide particles with a particle size of 20-50nm in the special sizing agent is 3%-8%, and they are evenly dispersed in the base solution after ultrasonic dispersion for 30-60min. The particles can improve the UV resistance, wear resistance and chemical corrosion resistance of the fiber cloth, and meet the requirements of electronic grade applications for material durability and stability. The coating amount of the special sizing agent is 0.5%-1.5% of the mass of the quartz glass fiber. This range can ensure that the sizing agent can play an effective role, such as improving the surface properties of the fiber cloth and enhancing the bonding force between fibers, and avoid affecting the electrical properties and other properties of the fiber cloth due to excessive coating.

[0035] The present invention also provides a performance testing method for electronic-grade quartz glass fiber cloth, which is used to evaluate the applicability of the fiber cloth in electronic-grade applications, and specifically comprises the following steps: S1: Conduct dielectric property tests on the prepared electronic grade quartz glass fiber cloth, including the measurement of dielectric constant and dielectric loss tangent; S2: Test the tensile strength and elastic modulus of electronic grade quartz glass fiber cloth; S3: Conduct temperature resistance test on electronic grade quartz glass fiber cloth to test its performance stability under high temperature (such as 200℃) and low temperature (such as -50℃) environments; S4: Test the chemical corrosion resistance of electronic grade quartz glass fiber cloth by immersing it in different chemical reagents (such as acid, alkali, organic solvents) and observing the changes in its performance.

[0036] Specifically, in step S1, a professional dielectric performance tester is used to test the dielectric performance of electronic grade quartz glass fiber cloth, and the test frequency range is 1kHz-1MHz, and the dielectric constant and dielectric loss tangent value at different frequencies are measured. For the dielectric constant, it is required to be maintained between 3.2-3.8 within the test frequency range; for the dielectric loss tangent value, it should be less than 0.01 to ensure that the fiber cloth has good signal transmission performance in the electronic circuit.

[0037] Specifically, in step S2, a universal material testing machine is used to test the tensile strength and elastic modulus of the electronic grade quartz glass fiber cloth at a test rate of 5 mm / min. The tensile strength should be above 1000 MPa and the elastic modulus should be above 70 GPa to ensure that the fiber cloth can withstand a certain mechanical load during use.

[0038] Specifically, in step S3, the electronic grade quartz glass fiber is placed in a high temperature test box and a low temperature test box, and maintained at 200°C and -50°C for 24 hours respectively, and the changes in its size, mechanical properties and electrical properties are observed. Under high temperature and low temperature environments, the size change of the fiber cloth should be less than 0.5%, and the change rate of mechanical properties and electrical properties should be less than 10%, so as to ensure its stability under different temperature environments.

[0039] Specifically, in step S4, the electronic grade quartz glass fiber cloth is immersed in 1 mol / L hydrochloric acid, sodium hydroxide solution and common organic solvent (such as ethanol, acetone) respectively for 24 hours, and the changes in the appearance, weight, mechanical properties and electrical properties of the fiber cloth are observed. After immersion, the appearance of the fiber cloth should not change significantly, the weight change is less than 1%, and the change rate of mechanical properties and electrical properties is less than 5%, indicating that it has good chemical corrosion resistance.

[0040] The present invention also provides an application of electronic grade quartz glass fiber cloth in electronic packaging. The prepared electronic grade quartz glass fiber cloth is used as a packaging material for electronic components. The specific operation is as follows: S1: Cut the electronic grade quartz glass fiber cloth into suitable sizes according to the size and packaging requirements of the electronic components, with a cutting accuracy of ±0.1mm; S2: Wrap the cut electronic grade quartz glass fiber cloth around the electronic components and fix them with special packaging glue; S3: Perform performance tests on packaged electronic components, including electrical performance tests and reliability tests.

[0041] Specifically, in step S1, a high-precision laser cutting machine is used to cut the electronic-grade quartz glass fiber cloth into suitable sizes, ensuring that the precision of the cutting size is ±0.1 mm to meet the packaging requirements of electronic components of different sizes.

[0042] Specifically, in step S2, the packaging glue used is an epoxy resin packaging glue with good bonding and insulation properties. The cut electronic-grade quartz glass fiber cloth is tightly wrapped around the electronic component to form a good packaging structure.

[0043] Specifically, in step S3, the packaged electronic components are subjected to electrical performance tests, such as insulation resistance and breakdown voltage. The insulation resistance should be greater than 10¹²Ω, and the breakdown voltage should be greater than 8kV. At the same time, reliability tests are performed, including temperature cycle tests, humidity tests, and vibration tests, to ensure that the performance of the packaged electronic components is stable and reliable under different environmental conditions.

[0044] Example 1 The electronic grade quartz glass fiber cloth of this embodiment comprises the following components: Quartz glass fiber and special sizing agent. Prepared by the following steps: S1: Select high-purity quartz sand (purity is 99.999%), put it into an arc furnace, melt it at 2850°C, and obtain uniform quartz glass liquid for standby use; S2: Precision filtration of the molten quartz glass liquid using a ceramic filter with a pore size of 0.3 μm at a filtration pressure of 0.3 MPa to remove impurities and unmelted particles to ensure the high purity of the glass liquid; S3: placing the filtered quartz glass liquid in a rotating stirring device and stirring at a speed of 80 rpm for 45 minutes to ensure the uniformity of the glass liquid composition and temperature; S4: Preparation of special infiltrant: S41: Dissolve γ-aminopropyltriethoxysilane (as a silane coupling agent), polytetrafluoroethylene powder (as a lubricant), and quaternary ammonium salt compounds (as an antistatic agent) in deionized water according to a mass ratio of 2.5:1:1:12 to prepare a basic solution; S42: Add nano-scale titanium dioxide particles with a particle size of 35 nm to the basic solution, and ultrasonically disperse them in an ultrasonic dispersion device (power of 800 W, frequency of 40 kHz) for 45 minutes to evenly disperse the nano-particles to prepare a special wetting agent; S5: The quartz glass liquid in step S3 is passed through a platinum-rhodium alloy leak plate (aperture accuracy is ±0.05 μm) and drawn into a quartz glass fiber with a diameter of 4 μm at a speed of 1200 m / min and a flow rate of 1.0 mL / min. At the same time, the special sizing agent in step S4 is evenly coated on the surface of the newly drawn fiber, and the coating amount of the special sizing agent is 1.0% of the mass of the quartz glass fiber; S6: Bundle the quartz glass fibers coated with the sizing agent and weave them into electronic grade quartz glass fiber cloth with a warp and weft density of 35×35 strands / cm² through a weaving device with a computer control system; S7: subjecting the fiber cloth embryo to high temperature sintering treatment, treating it at a high temperature of 900° C. for 45 minutes, using a high temperature sintering furnace with zone heating and argon atmosphere to remove excess impregnating agent residue, and obtaining electronic grade quartz glass fiber cloth; S8: subjecting the electronic grade quartz glass fiber cloth sintered at high temperature to electron beam irradiation treatment, using a high energy electron beam accelerator (electron beam energy of 2 MeV) in a vacuum environment, to irradiate at a dose of 15 kGy to improve the electrical properties of the fiber cloth; S9: The fiber cloth treated with electron beam irradiation is cleaned with ultrapure water, the resistivity of which is 18.2 MΩ·cm, in an ultrasonic cleaning tank (ultrasonic frequency is 60 kHz, cleaning time is 15 min), and then dried with low-humidity nitrogen in a clean environment (cleanliness level is ISO 4) to ensure that it meets the electronic grade cleanliness requirements.

[0045] The electronic grade quartz glass fiber cloth is used for electronic packaging, specifically including: S1: Cut the electronic grade quartz glass fiber cloth into appropriate size with a cutting accuracy of ±0.1mm; S2: Wrap the cut electronic grade quartz glass fiber cloth around the electronic components and fix them with epoxy resin encapsulation glue; S3: Performance tests are performed on packaged electronic components, including electrical performance tests and reliability tests, where the insulation resistance is greater than 10¹²Ω and the breakdown voltage is greater than 8kV.

[0046] Example 2 The electronic grade quartz glass fiber cloth of this embodiment comprises: quartz glass fiber and special sizing agent. The preparation process is as follows: S1: Select high-purity quartz sand (purity is 99.999%), put it into an arc furnace, melt it at 2900°C, and obtain uniform quartz glass liquid for standby use; S2: The molten quartz glass liquid is precisely filtered using a ceramic filter with a pore size of 0.4 μm and a filtration pressure of 0.4 MPa to remove impurities and unmelted particles to ensure the high purity of the glass liquid; S3: placing the filtered quartz glass liquid in a rotating stirring device and stirring at a speed of 70 rpm for 50 minutes to ensure the uniformity of the glass liquid composition and temperature; S4: Preparation of special infiltrant: S41: dissolving γ-aminopropyltriethoxysilane (as a silane coupling agent), polytetrafluoroethylene powder (as a lubricant), and a quaternary ammonium salt compound (as an antistatic agent) in deionized water according to a mass ratio of 2:1:1:13 to prepare a basic solution; S42: adding nano-sized titanium dioxide particles with a particle size of 40 nm to the base solution, and ultrasonically dispersing the particles in an ultrasonic dispersing device (power of 800 W, frequency of 40 kHz) for 50 min to uniformly disperse the nano-particles to prepare a special wetting agent; S5: The quartz glass liquid in step S3 is passed through a platinum-rhodium alloy leak plate (aperture accuracy is ±0.05 μm) and drawn into a quartz glass fiber with a diameter of 4.5 μm at a speed of 1300 m / min and a flow rate of 1.1 mL / min. At the same time, the special sizing agent in step S4 is evenly coated on the surface of the newly drawn fiber, and the coating amount of the special sizing agent is 1.2% of the mass of the quartz glass fiber; S6: Bundle the quartz glass fibers coated with the sizing agent and weave them into electronic grade quartz glass fiber cloth with a warp and weft density of 38×38 strands / cm² through a weaving device with a computer control system; S7: performing high-temperature sintering treatment on the fiber cloth embryo at a high temperature of 950° C. for 50 minutes, using a high-temperature sintering furnace with zone heating and argon atmosphere to remove excess impregnating agent residues, thereby obtaining electronic grade quartz glass fiber cloth; S8: subjecting the electronic grade quartz glass fiber cloth sintered at high temperature to electron beam irradiation treatment, using a high energy electron beam accelerator (electron beam energy of 2.5 MeV) in a vacuum environment, to irradiate at an irradiation dose of 18 kGy to improve the electrical properties of the fiber cloth; S9: The fiber cloth treated with electron beam irradiation is cleaned with ultrapure water, the resistivity of which is 18.2 MΩ·cm, in an ultrasonic cleaning tank (ultrasonic frequency is 60 kHz, cleaning time is 18 min), and then dried with low-humidity nitrogen in a clean environment (cleanliness level is ISO 4) to ensure that it meets the electronic grade cleanliness requirements.

[0047] The electronic grade quartz glass fiber cloth is used for electronic packaging, specifically including: S1: Cut the electronic grade quartz glass fiber cloth into appropriate size with a cutting accuracy of ±0.1mm; S2: Wrap the cut electronic grade quartz glass fiber cloth around the electronic components and fix them with epoxy resin encapsulation glue; S3: Performance tests are performed on packaged electronic components, including electrical performance tests and reliability tests, where the insulation resistance is greater than 10¹²Ω and the breakdown voltage is greater than 8kV.

[0048] Example 3 The electronic grade quartz glass fiber cloth of this embodiment comprises: quartz glass fiber and special sizing agent. The preparation process is as follows: S1: Select high-purity quartz sand (purity is 99.999%), put it into an arc furnace, melt it at 2800°C, and obtain uniform quartz glass liquid for use; S2: The molten quartz glass liquid is precisely filtered using a ceramic filter with a pore size of 0.2μm at a filtration pressure of 0.25MPa to remove impurities and unmelted particles to ensure the high purity of the glass liquid; S3: placing the filtered quartz glass liquid in a rotating stirring device and stirring at a speed of 60 rpm for 35 minutes to ensure the uniformity of the glass liquid composition and temperature; S4: Preparation of special infiltrant: S41: dissolving γ-aminopropyltriethoxysilane (as a silane coupling agent), polytetrafluoroethylene powder (as a lubricant), and a quaternary ammonium salt compound (as an antistatic agent) in deionized water according to a mass ratio of 3:1:1:11 to prepare a basic solution; S42: adding nano-sized titanium dioxide particles with a particle size of 25 nm to the base solution, and ultrasonically dispersing the nano-particles for 35 minutes in an ultrasonic dispersing device (power of 800 W, frequency of 40 kHz) to uniformly disperse the nano-particles to prepare a special wetting agent; S5: The quartz glass liquid in step S3 is passed through a platinum-rhodium alloy leak plate (aperture accuracy is ±0.05 μm) and drawn into a quartz glass fiber with a diameter of 3.5 μm at a speed of 1100 m / min and a flow rate of 0.9 mL / min. At the same time, the special sizing agent in step S4 is evenly coated on the surface of the newly drawn fiber, and the coating amount of the special sizing agent is 0.8% of the mass of the quartz glass fiber; S6: Bundle the quartz glass fibers coated with the sizing agent and weave them into electronic grade quartz glass fiber cloth with a warp and weft density of 32×32 strands / cm² through a weaving device with a computer control system; S7: subjecting the fiber cloth embryo to high temperature sintering treatment at a high temperature of 850° C. for 35 minutes, using a high temperature sintering furnace with zone heating and argon atmosphere to remove excess impregnating agent residues, thereby obtaining electronic grade quartz glass fiber cloth; S8: subjecting the electronic grade quartz glass fiber cloth sintered at high temperature to electron beam irradiation treatment, using a high energy electron beam accelerator (electron beam energy of 1.5 MeV) in a vacuum environment, to irradiate at a dose of 12 kGy to improve the electrical properties of the fiber cloth; S9: The fiber cloth treated with electron beam irradiation is cleaned with ultrapure water, the resistivity of which is 18.2 MΩ·cm, in an ultrasonic cleaning tank (ultrasonic frequency is 60 kHz, cleaning time is 12 min), and then dried with low-humidity nitrogen in a clean environment (cleanliness level is ISO 4) to ensure that it meets the electronic grade cleanliness requirements.

[0049] The electronic grade quartz glass fiber cloth is used for electronic packaging, specifically including: S1: Cut the electronic grade quartz glass fiber cloth into appropriate size with a cutting accuracy of ±0.1mm; S2: Wrap the cut electronic-grade quartz glass fiber cloth around the electronic components and fix them with epoxy resin packaging glue; S3: Perform performance tests on the packaged electronic components, including electrical performance tests and reliability tests, where the insulation resistance is greater than 10¹²Ω and the breakdown voltage is greater than 8kV.

[0050] Example 4 The electronic grade quartz glass fiber cloth of this embodiment comprises: quartz glass fiber and special sizing agent. The preparation process is as follows: S1: Select high-purity quartz sand (purity is 99.999%), put it into an arc furnace, melt it at 2950°C, and obtain uniform quartz glass liquid for standby use; S2: The molten quartz glass liquid is precisely filtered using a ceramic filter with a pore size of 0.5 μm at a filtration pressure of 0.45 MPa to remove impurities and unmelted particles to ensure the high purity of the glass liquid; S3: placing the filtered quartz glass liquid in a rotating stirring device and stirring at a speed of 90 rpm for 55 minutes to ensure the uniformity of the glass liquid composition and temperature; S4: Preparation of special infiltrant: S41: dissolving γ-aminopropyltriethoxysilane (as a silane coupling agent), polytetrafluoroethylene powder (as a lubricant), and a quaternary ammonium salt compound (as an antistatic agent) in deionized water according to a mass ratio of 2.8:1:1:14 to prepare a basic solution; S42: adding nano-sized titanium dioxide particles with a particle size of 45 nm to the base solution, and ultrasonically dispersing the particles for 55 min in an ultrasonic dispersing device (power of 800 W, frequency of 40 kHz) to uniformly disperse the nano-particles to prepare a special wetting agent; S5: The quartz glass liquid in step S3 is passed through a platinum-rhodium alloy leak plate (aperture accuracy is ±0.05 μm) and drawn into a quartz glass fiber with a diameter of 4.8 μm at a speed of 1400 m / min and a flow rate of 1.2 mL / min. At the same time, the special sizing agent in step S4 is evenly coated on the surface of the newly drawn fiber, and the coating amount of the special sizing agent is 1.4% of the mass of the quartz glass fiber; S6: Bundle the quartz glass fibers coated with the sizing agent and weave them into electronic grade quartz glass fiber cloth with a warp and weft density of 40×40 strands / cm² through a weaving device with a computer control system; S7: subjecting the fiber cloth embryo to high temperature sintering treatment at a high temperature of 1000° C. for 55 minutes, using a high temperature sintering furnace with zone heating and argon atmosphere to remove excess impregnating agent residues, thereby obtaining electronic grade quartz glass fiber cloth; S8: subjecting the electronic grade quartz glass fiber cloth sintered at high temperature to electron beam irradiation treatment, using a high energy electron beam accelerator (electron beam energy of 2.8 MeV) in a vacuum environment, to irradiate at a dose of 19 kGy to improve the electrical properties of the fiber cloth; S9: The fiber cloth treated with electron beam irradiation is cleaned with ultrapure water, the resistivity of which is 18.2 MΩ·cm, in an ultrasonic cleaning tank (ultrasonic frequency is 60 kHz, cleaning time is 20 min), and then dried with low-humidity nitrogen in a clean environment (cleanliness level is ISO 4) to ensure that it meets the electronic grade cleanliness requirements.

[0051] The electronic grade quartz glass fiber cloth is used for electronic packaging, specifically including: S1: Cut the electronic grade quartz glass fiber cloth into appropriate size with a cutting accuracy of ±0.1mm; S2: Wrap the cut electronic grade quartz glass fiber cloth around the electronic components and fix them with epoxy resin encapsulation glue; S3: Performance tests are performed on packaged electronic components, including electrical performance tests and reliability tests, where the insulation resistance is greater than 10¹²Ω and the breakdown voltage is greater than 8kV.

[0052] Example 5 The electronic grade quartz glass fiber cloth of this embodiment comprises: quartz glass fiber and special sizing agent. The preparation process is as follows: S1: Select high-purity quartz sand (purity is 99.999%), put it into an arc furnace, melt it at 2880°C, and obtain uniform quartz glass liquid for standby use; S2: The molten quartz glass liquid is precisely filtered using a ceramic filter with a pore size of 0.1 μm at a filtration pressure of 0.2 MPa to remove impurities and unmelted particles to ensure the high purity of the glass liquid; S3: placing the filtered quartz glass liquid in a rotating stirring device and stirring at a speed of 55 rpm for 32 minutes to ensure the uniformity of the glass liquid composition and temperature; S4: Preparation of special infiltrant: S41: dissolving γ-aminopropyltriethoxysilane (as a silane coupling agent), polytetrafluoroethylene powder (as a lubricant), and a quaternary ammonium salt compound (as an antistatic agent) in deionized water according to a mass ratio of 2.2:1:1:10.5 to prepare a basic solution; S42: adding nano-sized titanium dioxide particles with a particle size of 22 nm to the base solution, and ultrasonically dispersing the nano-particles for 32 minutes in an ultrasonic dispersing device (power of 800 W, frequency of 40 kHz) to uniformly disperse the nano-particles to prepare a special wetting agent; S5: The quartz glass liquid in step S3 is passed through a platinum-rhodium alloy leak plate (aperture accuracy is ±0.05 μm) and drawn into a quartz glass fiber with a diameter of 3.2 μm at a speed of 1050 m / min and a flow rate of 0.85 mL / min. At the same time, the special sizing agent in step S4 is evenly coated on the surface of the newly drawn fiber, and the coating amount of the special sizing agent is 0.6% of the mass of the quartz glass fiber; S6: Bundle the quartz glass fibers coated with the sizing agent and weave them into electronic grade quartz glass fiber cloth with a warp and weft density of 30×30 strands / cm² through a weaving device with a computer control system; S7: subjecting the fiber cloth embryo to high temperature sintering treatment at a high temperature of 820° C. for 32 minutes, using a high temperature sintering furnace with zone heating and argon atmosphere to remove excess impregnating agent residues, thereby obtaining electronic grade quartz glass fiber cloth; S8: subjecting the electronic grade quartz glass fiber cloth sintered at high temperature to electron beam irradiation treatment, using a high energy electron beam accelerator (electron beam energy of 1.2 MeV) in a vacuum environment, to irradiate at an irradiation dose of 11 kGy to improve the electrical properties of the fiber cloth; S9: The fiber cloth treated with electron beam irradiation is cleaned with ultrapure water, the resistivity of which is 18.2 MΩ·cm, in an ultrasonic cleaning tank (ultrasonic frequency is 60 kHz, cleaning time is 10 min), and then dried with low-humidity nitrogen in a clean environment (cleanliness level is ISO 4) to ensure that it meets the electronic grade cleanliness requirements.

[0053] The electronic grade quartz glass fiber cloth is used for electronic packaging, specifically including: S1: Cut the electronic grade quartz glass fiber cloth into appropriate size with a cutting accuracy of ±0.1mm; S2: Wrap the cut electronic grade quartz glass fiber cloth around the electronic components and fix them with epoxy resin encapsulation glue; S3: Performance tests are performed on packaged electronic components, including electrical performance tests and reliability tests, where the insulation resistance is greater than 10¹²Ω and the breakdown voltage is greater than 8kV.

[0054] Example 6 The electronic grade quartz glass fiber cloth of this embodiment comprises: quartz glass fiber and special sizing agent. The preparation process is as follows: S1: Select high-purity quartz sand (purity is 99.999%), put it into an arc furnace, melt it at 2920°C, and obtain uniform quartz glass liquid for standby use; S2: The molten quartz glass liquid is precisely filtered using a ceramic filter with a pore size of 0.35 μm and a filtration pressure of 0.35 MPa to remove impurities and unmelted particles to ensure the high purity of the glass liquid; S3: placing the filtered quartz glass liquid in a rotating stirring device and stirring at a speed of 75 rpm for 48 minutes to ensure the uniformity of the glass liquid composition and temperature; S4: Preparation of special infiltrant: S41: dissolving γ-aminopropyltriethoxysilane (as a silane coupling agent), polytetrafluoroethylene powder (as a lubricant), and a quaternary ammonium salt compound (as an antistatic agent) in deionized water according to a mass ratio of 2.6:1:1:13.5 to prepare a basic solution; S42: adding nano-sized titanium dioxide particles with a particle size of 38 nm to the base solution, and ultrasonically dispersing the particles for 48 min in an ultrasonic dispersing device (power of 800 W, frequency of 40 kHz) to uniformly disperse the nano-particles to prepare a special wetting agent; S5: The quartz glass liquid in step S3 is passed through a platinum-rhodium alloy leak plate (aperture accuracy is ±0.05 μm) and drawn into a quartz glass fiber with a diameter of 4.2 μm at a speed of 1250 m / min and a flow rate of 1.05 mL / min. At the same time, the special sizing agent in step S4 is evenly coated on the surface of the newly drawn fiber, and the coating amount of the special sizing agent is 1.1% of the mass of the quartz glass fiber; S6: Bundle the quartz glass fibers coated with the sizing agent and weave them into electronic grade quartz glass fiber cloth with a warp and weft density of 36×36 strands / cm² through a weaving device with a computer control system; S7: subjecting the fiber cloth embryo to high temperature sintering treatment at a high temperature of 920° C. for 48 minutes, using a high temperature sintering furnace with zone heating and argon atmosphere to remove excess impregnating agent residues, thereby obtaining electronic grade quartz glass fiber cloth; S8: subjecting the electronic grade quartz glass fiber cloth sintered at high temperature to electron beam irradiation treatment, using a high energy electron beam accelerator (electron beam energy of 2.2 MeV) in a vacuum environment, to irradiate at an irradiation dose of 16 kGy to improve the electrical properties of the fiber cloth; S9: The fiber cloth treated with electron beam irradiation is cleaned with ultrapure water, the resistivity of which is 18.2 MΩ·cm, in an ultrasonic cleaning tank (ultrasonic frequency is 60 kHz, cleaning time is 16 min), and then dried with low-humidity nitrogen in a clean environment (cleanliness level is ISO 4) to ensure that it meets the electronic grade cleanliness requirements.

[0055] The electronic grade quartz glass fiber cloth is used for electronic packaging, specifically including: S1: Cut the electronic grade quartz glass fiber cloth into appropriate size with a cutting accuracy of ±0.1mm; S2: Wrap the cut electronic grade quartz glass fiber cloth around the electronic components and fix them with epoxy resin encapsulation glue; S3: Performance tests are performed on packaged electronic components, including electrical performance tests and reliability tests, where the insulation resistance is greater than 10¹²Ω and the breakdown voltage is greater than 8kV.

[0056] Example 7 The electronic grade quartz glass fiber cloth of this embodiment comprises: quartz glass fiber and special sizing agent. The preparation process is as follows: S1: Select high-purity quartz sand (purity is 99.999%), put it into an arc furnace, melt it at 2830°C, and obtain uniform quartz glass liquid for standby use; S2: The molten quartz glass liquid is precisely filtered using a ceramic filter with a pore size of 0.45 μm and a filtration pressure of 0.42 MPa to remove impurities and unmelted particles to ensure the high purity of the glass liquid; S3: placing the filtered quartz glass liquid in a rotating stirring device and stirring at a speed of 65 rpm for 38 minutes to ensure the uniformity of the glass liquid composition and temperature; S4: Preparation of special infiltrant: S41: dissolving γ-aminopropyltriethoxysilane (as a silane coupling agent), polytetrafluoroethylene powder (as a lubricant), and a quaternary ammonium salt compound (as an antistatic agent) in deionized water according to a mass ratio of 2.4:1:1:12.5 to prepare a basic solution; S42: adding nano-sized titanium dioxide particles with a particle size of 42 nm to the base solution, and ultrasonically dispersing the nano-particles for 38 minutes in an ultrasonic dispersing device (power of 800 W, frequency of 40 kHz) to uniformly disperse the nano-particles to prepare a special wetting agent; S5: The quartz glass liquid in step S3 is passed through a platinum-rhodium alloy leak plate (aperture accuracy is ±0.05 μm) and drawn into a quartz glass fiber with a diameter of 3.8 μm at a speed of 1150 m / min and a flow rate of 0.95 mL / min. At the same time, the special sizing agent in step S4 is evenly coated on the surface of the fiber just drawn, and the coating amount of the special sizing agent is 0.9% of the mass of the quartz glass fiber; S6: Bundle the quartz glass fibers coated with the sizing agent and weave them into electronic grade quartz glass fiber cloth with a warp and weft density of 34×34 strands / cm² through a weaving device with a computer control system; S7: The fiber cloth embryo is subjected to high temperature sintering treatment at a high temperature of 880° C. for 42 minutes, using a high temperature sintering furnace with zone heating and argon atmosphere to remove excess impregnating agent residues, thereby obtaining electronic grade quartz glass fiber cloth; S8: subjecting the electronic grade quartz glass fiber cloth sintered at high temperature to electron beam irradiation treatment, using a high energy electron beam accelerator (electron beam energy of 1.8 MeV) in a vacuum environment, to irradiate at a dose of 14 kGy to improve the electrical properties of the fiber cloth; S9: The fiber cloth treated with electron beam irradiation is cleaned with ultrapure water, the resistivity of which is 18.2 MΩ·cm, in an ultrasonic cleaning tank (ultrasonic frequency is 60 kHz, cleaning time is 14 min), and then dried with low-humidity nitrogen in a clean environment (cleanliness level is ISO 4) to ensure that it meets the electronic grade cleanliness requirements.

[0057] The electronic grade quartz glass fiber cloth is used for electronic packaging, specifically including: S1: Cut the electronic grade quartz glass fiber cloth into appropriate size with a cutting accuracy of ±0.1mm; S2: Wrap the cut electronic grade quartz glass fiber cloth around the electronic components and fix them with epoxy resin encapsulation glue; S3: Performance tests are performed on packaged electronic components, including electrical performance tests and reliability tests, where the insulation resistance is greater than 10¹²Ω and the breakdown voltage is greater than 8kV.

[0058] Example 8 The electronic grade quartz glass fiber cloth of this embodiment comprises: quartz glass fiber and special sizing agent. The preparation process is as follows: S1: Select high-purity quartz sand (purity is 99.999%), put it into an arc furnace, melt it at 2980°C, and obtain uniform quartz glass liquid for standby use; S2: The molten quartz glass liquid is precisely filtered using a ceramic filter with a pore size of 0.25 μm at a filtration pressure of 0.28 MPa to remove impurities and unmelted particles to ensure the high purity of the glass liquid; S3: placing the filtered quartz glass liquid in a rotating stirring device and stirring at a speed of 85 rpm for 52 minutes to ensure the uniformity of the glass liquid composition and temperature; S4: Preparation of special infiltrant: S41: dissolving γ-aminopropyltriethoxysilane (as a silane coupling agent), polytetrafluoroethylene powder (as a lubricant), and a quaternary ammonium salt compound (as an antistatic agent) in deionized water according to a mass ratio of 2.7:1:1:11.5 to prepare a basic solution; S42: adding nano-sized titanium dioxide particles with a particle size of 28 nm to the base solution, and ultrasonically dispersing the particles for 52 minutes in an ultrasonic dispersing device (power of 800 W, frequency of 40 kHz) to uniformly disperse the nano-particles, thereby preparing a special wetting agent; S5: The quartz glass liquid in step S3 is passed through a platinum-rhodium alloy leak plate (aperture accuracy is ±0.05 μm) and drawn into a quartz glass fiber with a diameter of 4.6 μm at a speed of 1350 m / min and a flow rate of 1.15 mL / min. At the same time, the special sizing agent in step S4 is evenly coated on the surface of the newly drawn fiber, and the coating amount of the special sizing agent is 1.3% of the mass of the quartz glass fiber; S6: Bundle the quartz glass fibers coated with the sizing agent and weave them into electronic grade quartz glass fiber cloth with a warp and weft density of 39×39 strands / cm² through a weaving device with a computer control system; S7: subjecting the fiber cloth embryo to high temperature sintering treatment at a high temperature of 980° C. for 52 minutes, using a high temperature sintering furnace with zone heating and argon atmosphere to remove excess impregnating agent residues, thereby obtaining electronic grade quartz glass fiber cloth; S8: subjecting the electronic grade quartz glass fiber cloth sintered at high temperature to electron beam irradiation treatment, using a high energy electron beam accelerator (electron beam energy of 2.6 MeV) in a vacuum environment, to irradiate at a dose of 17 kGy to improve the electrical properties of the fiber cloth; S9: The fiber cloth treated with electron beam irradiation is cleaned with ultrapure water, the resistivity of which is 18.2 MΩ·cm, in an ultrasonic cleaning tank (ultrasonic frequency is 60 kHz, cleaning time is 17 min), and then dried with low-humidity nitrogen in a clean environment (cleanliness level is ISO 4) to ensure that it meets the electronic grade cleanliness requirements.

[0059] The electronic grade quartz glass fiber cloth is used for electronic packaging, specifically including: S1: Cut the electronic grade quartz glass fiber cloth into suitable size with a cutting accuracy of ±0.1mm; S2: Wrap the cut electronic grade quartz glass fiber cloth around the electronic components and fix them with epoxy resin encapsulation glue; S3: Performance tests are performed on packaged electronic components, including electrical performance tests and reliability tests, where the insulation resistance is greater than 10¹²Ω and the breakdown voltage is greater than 8kV.

[0060] Example 9 The electronic grade quartz glass fiber cloth of this embodiment comprises: quartz glass fiber and special sizing agent. The preparation process is as follows: S1: Select high-purity quartz sand (purity is 99.999%), put it into an arc furnace, melt it at 2860°C, and obtain uniform quartz glass liquid for use; S2: The molten quartz glass liquid is precisely filtered using a ceramic filter with a pore size of 0.15 μm at a filtration pressure of 0.22 MPa to remove impurities and unmelted particles to ensure the high purity of the glass liquid; S3: placing the filtered quartz glass liquid in a rotating stirring device and stirring at a speed of 58 rpm for 34 minutes to ensure the uniformity of the glass liquid composition and temperature; S4: Preparation of special infiltrant: S41: dissolving γ-aminopropyltriethoxysilane (as a silane coupling agent), polytetrafluoroethylene powder (as a lubricant), and a quaternary ammonium salt compound (as an antistatic agent) in deionized water according to a mass ratio of 2.3:1:1:10.8 to prepare a basic solution; S42: adding nano-sized titanium dioxide particles with a particle size of 24 nm to the base solution, and ultrasonically dispersing the nano-particles for 34 minutes in an ultrasonic dispersing device (power of 800 W, frequency of 40 kHz) to uniformly disperse the nano-particles to prepare a special wetting agent; S5: The quartz glass liquid in step S3 is passed through a platinum-rhodium alloy leak plate (aperture accuracy is ±0.05 μm) and drawn into a quartz glass fiber with a diameter of 3.4 μm at a speed of 1080 m / min and a flow rate of 0.88 mL / min. At the same time, the special sizing agent in step S4 is evenly coated on the surface of the newly drawn fiber, and the coating amount of the special sizing agent is 0.7% of the mass of the quartz glass fiber; S6: Bundle the quartz glass fibers coated with the sizing agent and weave them into electronic grade quartz glass fiber cloth with a warp and weft density of 31×31 strands / cm² through a weaving device with a computer control system; S7: subjecting the fiber cloth embryo to high temperature sintering treatment at a high temperature of 840° C. for 34 minutes, using a high temperature sintering furnace with zone heating and argon atmosphere to remove excess impregnating agent residues, thereby obtaining electronic grade quartz glass fiber cloth; S8: subjecting the electronic grade quartz glass fiber cloth sintered at high temperature to electron beam irradiation treatment, using a high energy electron beam accelerator (electron beam energy of 1.4 MeV) in a vacuum environment, to irradiate at an irradiation dose of 13 kGy to improve the electrical properties of the fiber cloth; S9: The fiber cloth treated with electron beam irradiation is cleaned with ultrapure water, the resistivity of which is 18.2 MΩ·cm, in an ultrasonic cleaning tank (ultrasonic frequency is 60 kHz, cleaning time is 11 min), and then dried with low-humidity nitrogen in a clean environment (cleanliness level is ISO 4) to ensure that it meets the electronic grade cleanliness requirements.

[0061] The electronic grade quartz glass fiber cloth is used for electronic packaging, specifically including: S1: Cut the electronic grade quartz glass fiber cloth into appropriate size with a cutting accuracy of ±0.1mm; S2: Wrap the cut electronic grade quartz glass fiber cloth around the electronic components and fix them with epoxy resin encapsulation glue; S3: Performance tests are performed on packaged electronic components, including electrical performance tests and reliability tests, where the insulation resistance is greater than 10¹²Ω and the breakdown voltage is greater than 8kV.

[0062] Example 10 The electronic grade quartz glass fiber cloth of this embodiment comprises: quartz glass fiber and special sizing agent. The preparation process is as follows: S1: Select high-purity quartz sand (purity is 99.999%), put it into an arc furnace, melt it at 2960°C, and obtain uniform quartz glass liquid for standby use; S2: The molten quartz glass liquid is precisely filtered using a ceramic filter with a pore size of 0.48 μm and a filtration pressure of 0.48 MPa to remove impurities and unmelted particles to ensure the high purity of the glass liquid; S3: placing the filtered quartz glass liquid in a rotating stirring device and stirring at a speed of 95 rpm for 58 minutes to ensure the uniformity of the glass liquid composition and temperature; S4: Preparation of special infiltrant: S41: dissolving γ-aminopropyltriethoxysilane (as a silane coupling agent), polytetrafluoroethylene powder (as a lubricant), and a quaternary ammonium salt compound (as an antistatic agent) in deionized water according to a mass ratio of 2.9:1:1:14.5 to prepare a basic solution; S42: adding nano-sized titanium dioxide particles with a particle size of 48 nm to the base solution, and ultrasonically dispersing the nano-particles for 58 min in an ultrasonic dispersing device (power of 800 W, frequency of 40 kHz) to uniformly disperse the nano-particles to prepare a special wetting agent; S5: The quartz glass liquid in step S3 is passed through a platinum-rhodium alloy leak plate (aperture accuracy is ±0.05 μm) and drawn into a quartz glass fiber with a diameter of 4.9 μm at a speed of 1450 m / min and a flow rate of 1.25 mL / min. At the same time, the special sizing agent in step S4 is evenly coated on the surface of the newly drawn fiber, and the coating amount of the special sizing agent is 1.5% of the mass of the quartz glass fiber; S6: Bundle the quartz glass fibers coated with the sizing agent and weave them into electronic grade quartz glass fiber cloth with a warp and weft density of 42×42 strands / cm² through a weaving device with a computer control system; S7: subjecting the fiber cloth embryo to high temperature sintering treatment at a high temperature of 1000° C. for 58 minutes, using a high temperature sintering furnace with zone heating and argon atmosphere to remove excess impregnating agent residues, thereby obtaining electronic grade quartz glass fiber cloth; S8: subjecting the electronic grade quartz glass fiber cloth sintered at high temperature to electron beam irradiation treatment, using a high energy electron beam accelerator (electron beam energy of 2.9 MeV) in a vacuum environment, to irradiate at an irradiation dose of 19.5 kGy to improve the electrical properties of the fiber cloth; S9: The fiber cloth treated with electron beam irradiation is cleaned with ultrapure water, the resistivity of which is 18.2 MΩ·cm, in an ultrasonic cleaning tank (ultrasonic frequency is 60 kHz, cleaning time is 19 min), and then dried with low-humidity nitrogen in a clean environment (cleanliness level is ISO 4) to ensure that it meets the electronic grade cleanliness requirements.

[0063] The electronic grade quartz glass fiber cloth is used for electronic packaging, specifically including: S1: Cut the electronic grade quartz glass fiber cloth into appropriate size with a cutting accuracy of ±0.1mm; S2: Wrap the cut electronic grade quartz glass fiber cloth around the electronic components and fix them with epoxy resin encapsulation glue; S3: Performance tests are performed on packaged electronic components, including electrical performance tests and reliability tests, where the insulation resistance is greater than 10¹²Ω and the breakdown voltage is greater than 8kV.

[0064] Comparative Example 1 The electronic grade quartz glass fiber cloth of this comparative example comprises: quartz glass fiber and special sizing agent. The preparation process is as follows: S1: Select high-purity quartz sand (purity is 99.99%), put it into an arc furnace, melt it at 2800°C, and obtain uniform quartz glass liquid for use; S2: The molten quartz glass liquid is precisely filtered using a ceramic filter with a pore size of 0.6 μm and a filtration pressure of 0.5 MPa to remove impurities and unmelted particles to ensure the high purity of the glass liquid; S3: placing the filtered quartz glass liquid in a rotating stirring device and stirring at a speed of 45 rpm for 30 minutes to ensure the uniformity of the glass liquid composition and temperature; S4: Preparation of special infiltrant: S41: dissolving γ-aminopropyltriethoxysilane (as a silane coupling agent), polytetrafluoroethylene powder (as a lubricant), and a quaternary ammonium salt compound (as an antistatic agent) in deionized water according to a mass ratio of 2:1:1:15 to prepare a basic solution; S42: adding nano-sized titanium dioxide particles with a particle size of 55 nm to the base solution, and ultrasonically dispersing the particles for 30 min in an ultrasonic dispersing device (power of 800 W, frequency of 40 kHz) to uniformly disperse the nano-particles to prepare a special wetting agent; S5: The quartz glass liquid in step S3 is passed through a platinum-rhodium alloy leak plate (aperture accuracy is ±0.1 μm) and drawn into a quartz glass fiber with a diameter of 3 μm at a speed of 900 m / min and a flow rate of 0.7 mL / min. At the same time, the special sizing agent in step S4 is evenly coated on the surface of the newly drawn fiber, and the coating amount of the special sizing agent is 0.5% of the mass of the quartz glass fiber; S6: Bundle the quartz glass fibers coated with the sizing agent and weave them into electronic grade quartz glass fiber cloth with a warp and weft density of 28×28 strands / cm² through a weaving device with a computer control system; S7: performing high-temperature sintering treatment on the fiber cloth embryo at a high temperature of 800° C. for 30 minutes, using a high-temperature sintering furnace with zone heating and argon atmosphere to remove excess impregnating agent residues, thereby obtaining electronic grade quartz glass fiber cloth; S8: subjecting the electronic grade quartz glass fiber cloth sintered at high temperature to electron beam irradiation treatment, using a high energy electron beam accelerator (electron beam energy of 1 MeV) in a vacuum environment, to irradiate at a dose of 10 kGy to improve the electrical properties of the fiber cloth; S9: The fiber cloth treated with electron beam irradiation is cleaned with ultrapure water, the resistivity of which is 18.2 MΩ·cm, in an ultrasonic cleaning tank (ultrasonic frequency is 60 kHz, cleaning time is 8 min), and then dried with low-humidity nitrogen in a clean environment (cleanliness level is ISO 4) to ensure that it meets the electronic grade cleanliness requirements.

[0065] The electronic grade quartz glass fiber cloth is used for electronic packaging, specifically including: S1: Cut the electronic grade quartz glass fiber cloth into appropriate size with a cutting accuracy of ±0.1mm; S2: Wrap the cut electronic grade quartz glass fiber cloth around the electronic components and fix them with epoxy resin encapsulation glue; S3: Performance tests are performed on packaged electronic components, including electrical performance tests and reliability tests, where the insulation resistance is greater than 10¹¹Ω and the breakdown voltage is greater than 7kV.

[0066] Comparative Example 2 The electronic grade quartz glass fiber cloth of this comparative example comprises: quartz glass fiber and special sizing agent. The preparation process is as follows: S1: Select high-purity quartz sand (purity is 99.99%), put it into an arc furnace, melt it at 3000°C, and obtain uniform quartz glass liquid for standby use; S2: The molten quartz glass liquid is precisely filtered using a ceramic filter with a pore size of 0.08 μm at a filtration pressure of 0.15 MPa to remove impurities and unmelted particles to ensure the high purity of the glass liquid; S3: placing the filtered quartz glass liquid in a rotating stirring device and stirring at a speed of 105 rpm for 60 minutes to ensure the uniformity of the glass liquid composition and temperature; S4: Preparation of special infiltrant: S41: dissolving γ-aminopropyltriethoxysilane (as a silane coupling agent), polytetrafluoroethylene powder (as a lubricant), and a quaternary ammonium salt compound (as an antistatic agent) in deionized water according to a mass ratio of 3:1:1:10 to prepare a basic solution; S42: adding nano-sized titanium dioxide particles with a particle size of 18 nm to the base solution, and ultrasonically dispersing the particles for 60 min in an ultrasonic dispersing device (power of 800 W, frequency of 40 kHz) to uniformly disperse the nano-particles to prepare a special wetting agent; S5: The quartz glass liquid in step S3 is passed through a platinum-rhodium alloy leak plate (aperture accuracy is ±0.03 μm) and drawn into a quartz glass fiber with a diameter of 5 μm at a speed of 1500 m / min and a flow rate of 1.3 mL / min. At the same time, the special sizing agent in step S4 is evenly coated on the surface of the newly drawn fiber, and the coating amount of the special sizing agent is 1.5% of the mass of the quartz glass fiber; S6: Bundle the quartz glass fibers coated with the sizing agent and weave them into electronic grade quartz glass fiber cloth with a warp and weft density of 45×45 strands / cm² through a weaving device with a computer control system; S7: performing high-temperature sintering treatment on the fiber cloth embryo at a high temperature of 1000° C. for 60 minutes, using a high-temperature sintering furnace with zone heating and argon atmosphere to remove excess impregnating agent residues, thereby obtaining electronic grade quartz glass fiber cloth; S8: subjecting the electronic grade quartz glass fiber cloth sintered at high temperature to electron beam irradiation treatment, using a high energy electron beam accelerator (electron beam energy of 2.5 MeV) in a vacuum environment, to irradiate at a dose of 20 kGy to improve the electrical properties of the fiber cloth; S9: The fiber cloth treated with electron beam irradiation is cleaned with ultrapure water, the resistivity of which is 18.2 MΩ·cm, in an ultrasonic cleaning tank (ultrasonic frequency is 60 kHz, cleaning time is 20 min), and then dried with low-humidity nitrogen in a clean environment (cleanliness level is ISO 4) to ensure that it meets the electronic grade cleanliness requirements.

[0067] The electronic grade quartz glass fiber cloth is used for electronic packaging, specifically including: S1: Cut the electronic grade quartz glass fiber cloth into appropriate size with a cutting accuracy of ±0.1mm; S2: Wrap the cut electronic grade quartz glass fiber cloth around the electronic components and fix them with epoxy resin encapsulation glue; S3: Performance tests are performed on packaged electronic components, including electrical performance tests and reliability tests, where the insulation resistance is greater than 10¹²Ω and the breakdown voltage is greater than 8kV.

[0068] Comparative Example 3 The electronic grade quartz glass fiber cloth of this comparative example comprises: quartz glass fiber and special sizing agent. The preparation process is as follows: S1: Select high-purity quartz sand (purity is 99.999%), put it into an arc furnace, melt it at 2820°C, and obtain uniform quartz glass liquid for standby use; S2: The molten quartz glass liquid is precisely filtered using a ceramic filter with a pore size of 0.55 μm at a filtration pressure of 0.4 MPa to remove impurities and unmelted particles to ensure the high purity of the glass liquid; S3: placing the filtered quartz glass liquid in a rotating stirring device and stirring at a speed of 50 rpm for 35 minutes to ensure the uniformity of the glass liquid composition and temperature; S4: Preparation of special infiltrant: S41: dissolving γ-aminopropyltriethoxysilane (as a silane coupling agent), polytetrafluoroethylene powder (as a lubricant), and a quaternary ammonium salt compound (as an antistatic agent) in deionized water according to a mass ratio of 2.2:1:1:11 to prepare a basic solution; S42: adding nano-sized titanium dioxide particles with a particle size of 52 nm to the base solution, and ultrasonically dispersing the nano-particles for 35 min in an ultrasonic dispersing device (power of 800 W, frequency of 40 kHz) to uniformly disperse the nano-particles to prepare a special wetting agent; S5: The quartz glass liquid in step S3 is passed through a platinum-rhodium alloy leak plate (aperture accuracy is ±0.06 μm) and drawn into a quartz glass fiber with a diameter of 3.2 μm at a speed of 1000 m / min and a flow rate of 0.8 mL / min. At the same time, the special wetting agent in step S4 is evenly coated on the surface of the newly drawn fiber, and the coating amount of the special wetting agent is 0.6% of the mass of the quartz glass fiber; S6: Bundle the quartz glass fibers coated with the sizing agent and weave them into electronic grade quartz glass fiber cloth with a warp and weft density of 30×30 strands / cm² through a weaving device with a computer control system; S7: subjecting the fiber cloth embryo to high temperature sintering treatment at a high temperature of 820° C. for 35 minutes, using a high temperature sintering furnace with zone heating and argon atmosphere to remove excess impregnating agent residues, thereby obtaining electronic grade quartz glass fiber cloth; S8: subjecting the electronic grade quartz glass fiber cloth sintered at high temperature to electron beam irradiation treatment, using a high energy electron beam accelerator (electron beam energy of 1.1 MeV) in a vacuum environment, to irradiate at an irradiation dose of 11 kGy to improve the electrical properties of the fiber cloth; S9: The fiber cloth treated with electron beam irradiation is cleaned with ultrapure water, the resistivity of which is 18.2 MΩ·cm, in an ultrasonic cleaning tank (ultrasonic frequency is 60 kHz, cleaning time is 10 min), and then dried with low-humidity nitrogen in a clean environment (cleanliness level is ISO 4) to ensure that it meets the electronic grade cleanliness requirements.

[0069] The electronic grade quartz glass fiber cloth is used for electronic packaging, specifically including: S1: Cut the electronic grade quartz glass fiber cloth into suitable size with a cutting accuracy of ±0.1mm; S2: Wrap the cut electronic grade quartz glass fiber cloth around the electronic components and fix them with epoxy resin encapsulation glue; S3: Performance tests are performed on packaged electronic components, including electrical performance tests and reliability tests, where the insulation resistance is greater than 10¹¹Ω and the breakdown voltage is greater than 7.5kV.

[0070] Comparative Example 4 The electronic grade quartz glass fiber cloth of this comparative example comprises: quartz glass fiber and special sizing agent. The preparation process is as follows: S1: Select high-purity quartz sand (purity is 99.999%), put it into an arc furnace, melt it at 2980°C, and obtain uniform quartz glass liquid for standby use; S2: The molten quartz glass liquid is precisely filtered using a ceramic filter with a pore size of 0.12 μm and a filtration pressure of 0.2 MPa to remove impurities and unmelted particles to ensure the high purity of the glass liquid; S3: placing the filtered quartz glass liquid in a rotating stirring device and stirring at a speed of 90 rpm for 50 minutes to ensure the uniformity of the glass liquid composition and temperature; S4: Preparation of special infiltrant: S41: dissolving γ-aminopropyltriethoxysilane (as a silane coupling agent), polytetrafluoroethylene powder (as a lubricant), and a quaternary ammonium salt compound (as an antistatic agent) in deionized water according to a mass ratio of 2.8:1:1:13 to prepare a basic solution; S42: adding nano-sized titanium dioxide particles with a particle size of 20 nm to the base solution, and ultrasonically dispersing the particles for 50 min in an ultrasonic dispersing device (power of 800 W, frequency of 40 kHz) to uniformly disperse the nano-particles, thereby preparing a special wetting agent; S5: The quartz glass liquid in step S3 is passed through a platinum-rhodium alloy leak plate (aperture accuracy is ±0.04 μm) and drawn into a quartz glass fiber with a diameter of 4.8 μm at a speed of 1400 m / min and a flow rate of 1.2 mL / min. At the same time, the special impregnating agent in step S4 is evenly coated on the surface of the fiber just drawn, and the coating amount of the special impregnating agent is 1.4% of the mass of the quartz glass fiber; S6: Bundle the quartz glass fibers coated with the sizing agent and weave them into electronic grade quartz glass fiber cloth with a warp and weft density of 40×40 strands / cm² through a weaving device with a computer control system; S7: subjecting the fiber cloth embryo to high temperature sintering treatment at a high temperature of 980° C. for 50 min, using a high temperature sintering furnace with zone heating and argon atmosphere to remove excess impregnating agent residues, thereby obtaining electronic grade quartz glass fiber cloth; S8: subjecting the electronic grade quartz glass fiber cloth sintered at high temperature to electron beam irradiation treatment, using a high energy electron beam accelerator (electron beam energy of 2.2 MeV) in a vacuum environment, to irradiate at an irradiation dose of 18 kGy to improve the electrical properties of the fiber cloth; S9: The fiber cloth treated with electron beam irradiation is cleaned with ultrapure water, the resistivity of which is 18.2 MΩ·cm, in an ultrasonic cleaning tank (ultrasonic frequency is 60 kHz, cleaning time is 16 min), and then dried with low-humidity nitrogen in a clean environment (cleanliness level is ISO 4) to ensure that it meets the electronic grade cleanliness requirements.

[0071] The electronic grade quartz glass fiber cloth is used for electronic packaging, specifically including: S1: Cut the electronic grade quartz glass fiber cloth into suitable size with a cutting accuracy of ±0.1mm; S2: Wrap the cut electronic grade quartz glass fiber cloth around the electronic components and fix them with epoxy resin encapsulation glue; S3: Performance tests are performed on packaged electronic components, including electrical performance tests and reliability tests, where the insulation resistance is greater than 10¹²Ω and the breakdown voltage is greater than 8kV.

[0072] Comparative Example 5 The electronic grade quartz glass fiber cloth of this comparative example comprises: quartz glass fiber and special sizing agent. The preparation process is as follows: S1: Select high-purity quartz sand (purity is 99.999%), put it into an arc furnace, melt it at 2850°C, and obtain uniform quartz glass liquid for standby use; S2: Precision filtration of the molten quartz glass liquid using a ceramic filter with a pore size of 0.3 μm at a filtration pressure of 0.3 MPa to remove impurities and unmelted particles to ensure the high purity of the glass liquid; S3: placing the filtered quartz glass liquid in a rotating stirring device and stirring at a speed of 70 rpm for 40 minutes to ensure the uniformity of the glass liquid composition and temperature; S4: Preparation of special infiltrant: S41: dissolving γ-aminopropyltriethoxysilane (as a silane coupling agent), polytetrafluoroethylene powder (as a lubricant), and a quaternary ammonium salt compound (as an antistatic agent) in deionized water according to a mass ratio of 2.5:1:1:12 to prepare a basic solution; S42: adding nano-sized titanium dioxide particles with a particle size of 35 nm to the base solution, and ultrasonically dispersing the nano-particles for 40 min in an ultrasonic dispersing device (power of 800 W, frequency of 40 kHz) to uniformly disperse the nano-particles to prepare a special wetting agent; S5: The quartz glass liquid in step S3 is passed through a platinum-rhodium alloy leak plate (aperture accuracy is ±0.05 μm) and drawn into a quartz glass fiber with a diameter of 4 μm at a speed of 1200 m / min and a flow rate of 1.0 mL / min. At the same time, the special sizing agent in step S4 is evenly coated on the surface of the newly drawn fiber, and the coating amount of the special sizing agent is 1.0% of the mass of the quartz glass fiber; S6: Bundle the quartz glass fibers coated with the sizing agent and weave them into electronic grade quartz glass fiber cloth with a warp and weft density of 35×35 strands / cm² through a weaving device with a computer control system; S7: subjecting the fiber cloth embryo to high temperature sintering treatment at a high temperature of 900° C. for 40 minutes, using a high temperature sintering furnace with zone heating and argon atmosphere to remove excess impregnating agent residues, thereby obtaining electronic grade quartz glass fiber cloth; S8: subjecting the electronic grade quartz glass fiber cloth sintered at high temperature to electron beam irradiation treatment, using a high energy electron beam accelerator (electron beam energy of 1.5 MeV) in a vacuum environment, to irradiate at a dose of 15 kGy to improve the electrical properties of the fiber cloth; S9: The fiber cloth treated with electron beam irradiation is cleaned with ultrapure water, the resistivity of which is 18.2 MΩ·cm, in an ultrasonic cleaning tank (ultrasonic frequency is 60 kHz, cleaning time is 12 min), and then dried in a clean environment (cleanliness level is ISO 4) under low pressure to ensure that it meets the electronic grade cleanliness requirements.

[0073] The electronic grade quartz glass fiber cloth is used for electronic packaging, specifically including: S1: Cut the electronic grade quartz glass fiber cloth into appropriate size with a cutting accuracy of ±0.1mm; S2: Wrap the cut electronic grade quartz glass fiber cloth around the electronic components and fix them with epoxy resin encapsulation glue; S3: Performance tests are performed on packaged electronic components, including electrical performance tests and reliability tests, where the insulation resistance is greater than 10¹¹Ω and the breakdown voltage is greater than 7.8kV.

[0074] Comparative Example 6 The electronic grade quartz glass fiber cloth of this comparative example comprises: quartz glass fiber and special sizing agent. The preparation process is as follows: S1: Select high-purity quartz sand (purity is 99.999%), put it into an arc furnace, melt it at 2920°C, and obtain uniform quartz glass liquid for standby use; S2: The molten quartz glass liquid is precisely filtered using a ceramic filter with a pore size of 0.4 μm and a filtration pressure of 0.4 MPa to remove impurities and unmelted particles to ensure the high purity of the glass liquid; S3: placing the filtered quartz glass liquid in a rotating stirring device and stirring at a speed of 80 rpm for 55 minutes to ensure the uniformity of the glass liquid composition and temperature; S4: Preparation of special infiltrant: S41: dissolving γ-aminopropyltriethoxysilane (as a silane coupling agent), polytetrafluoroethylene powder (as a lubricant), and a quaternary ammonium salt compound (as an antistatic agent) in deionized water according to a mass ratio of 2.7:1:1:14 to prepare a basic solution; S42: adding nano-sized titanium dioxide particles with a particle size of 45 nm to the base solution, and ultrasonically dispersing the particles for 55 min in an ultrasonic dispersing device (power of 800 W, frequency of 40 kHz) to uniformly disperse the nano-particles to prepare a special wetting agent; S5: The quartz glass liquid in step S3 is passed through a platinum-rhodium alloy leak plate (aperture accuracy is ±0.05 μm) and drawn into a quartz glass fiber with a diameter of 4.5 μm at a speed of 1300 m / min and a flow rate of 1.1 mL / min. At the same time, the special sizing agent in step S4 is evenly coated on the surface of the newly drawn fiber, and the coating amount of the special sizing agent is 1.2% of the mass of the quartz glass fiber; S6: Bundle the quartz glass fibers coated with the sizing agent and weave them into electronic grade quartz glass fiber cloth with a warp and weft density of 38×38 strands / cm² through a weaving device with a computer control system; S7: subjecting the fiber cloth embryo to high temperature sintering treatment at a high temperature of 950° C. for 55 minutes, using a high temperature sintering furnace with zone heating and argon atmosphere to remove excess impregnating agent residues, thereby obtaining electronic grade quartz glass fiber cloth; S8: subjecting the electronic grade quartz glass fiber cloth sintered at high temperature to electron beam irradiation treatment, using a high energy electron beam accelerator (electron beam energy of 2 MeV) in a vacuum environment, to irradiate at a dose of 17 kGy to improve the electrical properties of the fiber cloth; S9: The fiber cloth treated with electron beam irradiation is cleaned with ultrapure water, the resistivity of which is 18.2 MΩ·cm, in an ultrasonic cleaning tank (ultrasonic frequency is 60 kHz, cleaning time is 18 min), and then dried with low-humidity nitrogen in a clean environment (cleanliness level is ISO 4) to ensure that it meets the electronic grade cleanliness requirements.

[0075] The electronic grade quartz glass fiber cloth is used for electronic packaging, specifically including: S1: Cut the electronic grade quartz glass fiber cloth into suitable size with a cutting accuracy of ±0.1mm; S2: Wrap the cut electronic grade quartz glass fiber cloth around the electronic components and fix them with epoxy resin encapsulation glue; S3: Performance tests are performed on packaged electronic components, including electrical performance tests and reliability tests, where the insulation resistance is greater than 10¹²Ω and the breakdown voltage is greater than 8kV.

[0076] Comparative Example 7 The electronic grade quartz glass fiber cloth of this comparative example comprises: quartz glass fiber and special sizing agent. The preparation process is as follows: S1: Select high-purity quartz sand (purity is 99.999%), put it into an arc furnace, melt it at 2880°C, and obtain uniform quartz glass liquid for standby use; S2: The molten quartz glass liquid is precisely filtered using a ceramic filter with a pore size of 0.2μm at a filtration pressure of 0.25MPa to remove impurities and unmelted particles to ensure the high purity of the glass liquid; S3: placing the filtered quartz glass liquid in a rotating stirring device and stirring at a speed of 60 rpm for 30 minutes to ensure the uniformity of the glass liquid composition and temperature; S4: Preparation of special infiltrant: S41: dissolving γ-aminopropyltriethoxysilane (as a silane coupling agent), polytetrafluoroethylene powder (as a lubricant), and a quaternary ammonium salt compound (as an antistatic agent) in deionized water according to a mass ratio of 2.3:1:1:10.5 to prepare a basic solution; S42: adding nano-sized titanium dioxide particles with a particle size of 22 nm to the base solution, and ultrasonically dispersing the nano-particles for 30 min in an ultrasonic dispersing device (power of 800 W, frequency of 40 kHz) to uniformly disperse the nano-particles to prepare a special wetting agent; S5: The quartz glass liquid in step S3 is passed through a platinum-rhodium alloy leak plate (aperture accuracy is ±0.05 μm) and drawn into a quartz glass fiber with a diameter of 3.5 μm at a speed of 1100 m / min and a flow rate of 0.9 mL / min. At the same time, the special impregnating agent in step S4 is evenly coated on the surface of the fiber just drawn, and the coating amount of the special impregnating agent is quartz; S6: Bundle the quartz glass fibers coated with the sizing agent and weave them into electronic grade quartz glass fiber cloth with a warp and weft density of 32×32 strands / cm² through a weaving device with a computer control system; S7: performing high-temperature sintering treatment on the fiber cloth embryo at a high temperature of 850° C. for 30 minutes, using a high-temperature sintering furnace with zone heating and argon atmosphere to remove excess impregnating agent residues, thereby obtaining electronic grade quartz glass fiber cloth; S8: subjecting the electronic grade quartz glass fiber cloth sintered at high temperature to electron beam irradiation treatment, using a high energy electron beam accelerator (electron beam energy of 1.2 MeV) in a vacuum environment, to irradiate at a dose of 13 kGy to improve the electrical properties of the fiber cloth; S9: The fiber cloth treated with electron beam irradiation is cleaned with ultrapure water, the resistivity of which is 18.2 MΩ·cm, in an ultrasonic cleaning tank (ultrasonic frequency is 60 kHz, cleaning time is 10 min), and then dried with low-humidity nitrogen in a clean environment (cleanliness level is ISO 4) to ensure that it meets the electronic grade cleanliness requirements.

[0077] The electronic grade quartz glass fiber cloth is used for electronic packaging, specifically including: S1: Cut the electronic grade quartz glass fiber cloth into appropriate size with a cutting accuracy of ±0.1mm; S2: Wrap the cut electronic grade quartz glass fiber cloth around the electronic components and fix them with epoxy resin encapsulation glue; S3: Performance tests are performed on packaged electronic components, including electrical performance tests and reliability tests, where the insulation resistance is greater than 10¹¹Ω and the breakdown voltage is greater than 7.2kV.

[0078] Comparative Example 8 The electronic grade quartz glass fiber cloth of this comparative example comprises: quartz glass fiber and special sizing agent. The preparation process is as follows: S1: Select high-purity quartz sand (purity is 99.998%), put it into an arc furnace, melt it at 2800°C, and obtain uniform quartz glass liquid for use; S2: The molten quartz glass liquid is precisely filtered using a ceramic filter with a pore size of 0.5 μm at a filtration pressure of 0.45 MPa to remove impurities and unmelted particles to ensure the high purity of the glass liquid; S3: placing the filtered quartz glass liquid in a rotating stirring device and stirring at a speed of 55 rpm for 45 minutes to ensure the uniformity of the glass liquid composition and temperature; S4: Preparation of special infiltrant: S41: dissolving γ-aminopropyltriethoxysilane (as a silane coupling agent), polytetrafluoroethylene powder (as a lubricant), and a quaternary ammonium salt compound (as an antistatic agent) in deionized water according to a mass ratio of 2.1:1:1:12.5 to prepare a basic solution; S42: adding nano-sized titanium dioxide particles with a particle size of 50 nm to the base solution, and ultrasonically dispersing the particles for 45 min in an ultrasonic dispersing device (power of 800 W, frequency of 40 kHz) to uniformly disperse the nano-particles to prepare a special wetting agent; S5: The quartz glass liquid in step S3 is passed through a platinum-rhodium alloy leak plate (aperture accuracy is ±0.07 μm) and drawn into a quartz glass fiber with a diameter of 3.3 μm at a speed of 1050 m / min and a flow rate of 0.8 mL / min. At the same time, the special sizing agent in step S4 is evenly coated on the surface of the newly drawn fiber, and the coating amount of the special sizing agent is 0.6% of the mass of the quartz glass fiber; S6: Bundle the quartz glass fibers coated with the sizing agent and weave them into electronic grade quartz glass fiber cloth with a warp and weft density of 31×31 strands / cm² through a weaving device with a computer control system; S7: The fiber cloth embryo is subjected to high temperature sintering treatment at a high temperature of 820° C. for 45 minutes, using a high temperature sintering furnace with zone heating and argon atmosphere to remove excess impregnating agent residues, thereby obtaining electronic grade quartz glass fiber cloth; S8: subjecting the electronic grade quartz glass fiber cloth sintered at high temperature to electron beam irradiation treatment, using a high energy electron beam accelerator (electron beam energy of 1.4 MeV) in a vacuum environment, to irradiate at a dose of 12 kGy to improve the electrical properties of the fiber cloth; S9: The fiber cloth treated with electron beam irradiation is cleaned with ultrapure water, the resistivity of which is 18.2 MΩ·cm, in an ultrasonic cleaning tank (ultrasonic frequency is 60 kHz, cleaning time is 11 min), and then dried with low-humidity nitrogen in a clean environment (cleanliness level is ISO 4) to ensure that it meets the electronic grade cleanliness requirements.

[0079] The electronic grade quartz glass fiber cloth is used for electronic packaging, specifically including: S1: Cut the electronic grade quartz glass fiber cloth into appropriate size with a cutting accuracy of ±0.1mm; S2: Wrap the cut electronic grade quartz glass fiber cloth around the electronic components and fix them with epoxy resin encapsulation glue; S3: Performance tests are performed on packaged electronic components, including electrical performance tests and reliability tests, where the insulation resistance is greater than 10¹¹Ω and the breakdown voltage is greater than 7.5kV.

[0080] Comparative Example 9 The electronic grade quartz glass fiber cloth of this comparative example comprises: quartz glass fiber and special sizing agent. The preparation process is as follows: S1: Select high-purity quartz sand (purity is 99.999%), put it into an arc furnace, melt it at 2950°C, and obtain uniform quartz glass liquid for standby use; S2: The molten quartz glass liquid is precisely filtered using a ceramic filter with a pore size of 0.15 μm and a filtration pressure of 0.2 MPa to remove impurities and unmelted particles to ensure the high purity of the glass liquid; S3: placing the filtered quartz glass liquid in a rotating stirring device and stirring at a speed of 95 rpm for 35 min to ensure the uniformity of the glass liquid composition and temperature; S4: Preparation of special infiltrant: S41: dissolving γ-aminopropyltriethoxysilane (as a silane coupling agent), polytetrafluoroethylene powder (as a lubricant), and a quaternary ammonium salt compound (as an antistatic agent) in deionized water according to a mass ratio of 2.9:1:1:11.5 to prepare a basic solution; S42: adding nano-sized titanium dioxide particles with a particle size of 18 nm to the base solution, and ultrasonically dispersing the nano-particles for 35 min in an ultrasonic dispersing device (power of 800 W, frequency of 40 kHz) to uniformly disperse the nano-particles to prepare a special wetting agent; S5: The quartz glass liquid in step S3 is passed through a platinum-rhodium alloy leak plate (aperture accuracy is ±0.04 μm) and drawn into a quartz glass fiber with a diameter of 4.8 μm at a speed of 1450 m / min and a flow rate of 1.2 mL / min. At the same time, the special sizing agent in step S4 is evenly coated on the surface of the newly drawn fiber, and the coating amount of the special sizing agent is 1.4% of the mass of the quartz glass fiber; S6: Bundle the quartz glass fibers coated with the sizing agent and weave them into electronic grade quartz glass fiber cloth with a warp and weft density of 40×40 strands / cm² through a weaving device with a computer control system; S7: subjecting the fiber cloth embryo to high temperature sintering treatment at a high temperature of 980° C. for 35 minutes, using a high temperature sintering furnace with zone heating and argon atmosphere to remove excess impregnating agent residues, thereby obtaining electronic grade quartz glass fiber cloth; S8: subjecting the electronic grade quartz glass fiber cloth sintered at high temperature to electron beam irradiation treatment, using a high energy electron beam accelerator (electron beam energy of 2.2 MeV) in a vacuum environment, to irradiate at an irradiation dose of 18 kGy to improve the electrical properties of the fiber cloth; S9: The fiber cloth treated with electron beam irradiation is cleaned with ultrapure water, the resistivity of which is 18.2 MΩ·cm, in an ultrasonic cleaning tank (ultrasonic frequency is 60 kHz, cleaning time is 16 min), and then dried with low-humidity nitrogen in a clean environment (cleanliness level is ISO 4) to ensure that it meets the electronic grade cleanliness requirements.

[0081] The electronic grade quartz glass fiber cloth is used for electronic packaging, specifically including: S1: Cut the electronic grade quartz glass fiber cloth into appropriate size with a cutting accuracy of ±0.1mm; S2: Wrap the cut electronic grade quartz glass fiber cloth around the electronic components and fix them with epoxy resin encapsulation glue; S3: Perform performance tests on the packaged electronic components, including electrical performance tests and reliability tests, where the insulation resistance is greater than 10¹²Ω and the breakdown voltage is greater than 8kV. Using the test methods and relevant evaluation standards of the "Electronic Material Testing Standards", the electronic grade quartz glass fiber cloths prepared in the embodiments and comparative examples are tested for performance.

[0082] Test indicators include but are not limited to: Dielectric properties: The dielectric constant and dielectric loss at different frequencies are tested using a dielectric constant tester. The dielectric constant of the electronic grade quartz glass fiber cloth in the embodiment is required to be between 3.0 and 3.5 within the working frequency range, and the dielectric loss is lower than 0.005; the corresponding indicators in the comparative examples may deviate, and some may have a dielectric constant exceeding 3.5 or a dielectric loss higher than 0.005.

[0083] Mechanical properties: The tensile strength and bending strength tests were carried out using a universal material testing machine. The electronic grade quartz glass fiber cloth in the embodiment is expected to have a tensile strength of not less than 1500 MPa and a bending strength of not less than 200 MPa; the corresponding strengths in the comparative example may be lower than this value.

[0084] Heat resistance: The samples were placed in different high temperature environments to observe their size and performance changes. The electronic grade quartz glass fiber cloth in the embodiment was kept at 500°C for 24 hours, and the size change should be less than 1%, and the mechanical property decrease should not exceed 10%; the comparative example may have a larger size change and performance decrease.

[0085] Chemical resistance: The samples were immersed in different chemical reagents (such as acid, alkali, organic solvents) to observe the changes in appearance, quality and performance. After the electronic grade quartz glass fiber cloth in the embodiment was immersed for 24 hours, there was no obvious change in appearance, the quality change was less than 2%, and the performance degradation did not exceed 5%. The comparative example may have more serious changes in appearance, quality and performance degradation.

[0086] Table 1 Technical index test results of electronic grade quartz glass fiber cloth in the embodiment and comparative example

[0087] Table 2 Performance of electronic grade quartz glass fiber cloth in different environments of the embodiments and comparative examples

[0088] As can be seen from Table 1 and Table 2, for the electronic-grade quartz glass fiber cloth prepared by the method of the present invention, by precisely controlling the temperature of the electric arc furnace, using ceramic filters of different specifications, adjusting the stirring parameters, optimizing the composition and addition amount of the sizing agent, reasonably setting the speed and flow rate of fiber drawing, changing the weaving density, adjusting process parameters such as high-temperature sintering and electron beam irradiation, the excellent performance of the electronic-grade quartz glass fiber cloth is effectively guaranteed. When the fiber cloth is used as an electronic packaging material, it has good dielectric properties, mechanical properties and environmental adaptability. Among them, the dielectric constant is between 3.0 - 3.5 within the working frequency range, the dielectric loss is less than 0.005, the tensile strength is not less than 1500 MPa, and the flexural strength is not less than 200 MPa. At the same time, it shows good stability in different temperature environments. In the temperature range of -50°C to 500°C, the dimensional change does not exceed 1%, and the mechanical property degradation does not exceed 10%.

[0089] The electronic-grade quartz glass fiber cloth prepared by the method of the present invention exhibits good chemical resistance in different environments. After being immersed in chemical reagents such as acids, alkalis, and organic solvents for 24 hours, there is no obvious change in appearance, the mass change is less than 2%, and the performance degradation does not exceed 5%. Moreover, when the fiber cloth is used in electronic packaging applications and electrical performance tests and reliability tests are carried out, the insulation resistance is greater than 10¹² Ω, and the breakdown voltage is greater than 8 kV. It also performs excellently in reliability tests such as humidity, vibration, and temperature cycling, and can meet various performance requirements for electronic component packaging.

[0090] This enables the electronic-grade quartz glass fiber cloth prepared by the present invention to show significant advantages in the field of electronic packaging. It not only ensures the high performance of the material itself but also shows good stability and reliability under different environmental conditions. At the same time, it also provides a high-quality material option for the packaging of electronic components, improving the packaging quality and service life of electronic components, and providing a strong guarantee for the performance and reliability of electronic devices. At the same time, since the fiber cloth can meet different performance requirements by flexibly adjusting parameters during the preparation process, it provides multiple options for electronic packaging applications in different scenarios, which is conducive to promoting the technological development and product innovation of the electronic packaging industry.

[0091] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed by the present invention should be covered by the protection scope of the present invention.

Claims

1. A method for preparing electronic grade quartz glass fiber cloth, characterized in that: The following steps are involved: S1: Select high-purity quartz sand, put it into an arc furnace, melt it at a high temperature of 2800℃-3000℃, and obtain uniform quartz glass liquid for standby use; S2: Precision filter the molten quartz glass liquid using a ceramic filter with a pore size of 0.1-0.5μm to remove impurities and unmelted particles to ensure the high purity of the glass liquid; S3: homogenizing the filtered quartz glass liquid, placing the glass liquid in a rotating stirring device, and stirring at a speed of 50-100 rpm for 30-60 minutes to ensure the uniformity of the glass liquid composition and temperature; S4: prepare special infiltrant; S5: The quartz glass liquid in step S3 is passed through a platinum-rhodium alloy leak plate to be drawn into a quartz glass fiber with a diameter of 3-9 μm at a specific flow rate and speed, and at the same time, the special impregnating agent in step S4 is evenly coated on the surface of the just-drawn fiber; S6: Bundling the quartz glass fibers coated with the sizing agent, winding, arranging, twisting the raw fibers, and weaving them into electronic grade quartz glass fiber cloth embryos with specific warp and weft densities through a weaving device; S7: performing high-temperature sintering treatment on the fiber cloth embryo to remove excess impregnating agent residue to obtain electronic grade quartz glass fiber cloth; S8: subjecting the electronic grade quartz glass fiber cloth sintered at high temperature to electron beam irradiation treatment, with an irradiation dose of 10-20 kGy, to improve the electrical properties of the fiber cloth; S9: The fiber cloth treated with electron beam irradiation is cleaned with ultrapure water to remove surface impurities and by-products, and then dried in a clean environment after being treated with a coupling agent.

2. The preparation method according to claim 1, characterized in that: The step S4 comprises the following steps: S41: dissolving a silane coupling agent, a lubricant, and an antistatic agent in deionized water according to a mass ratio to prepare a basic solution; S42: Add nano-sized titanium dioxide particles to the base solution, and ultrasonically disperse the solution in an ultrasonic dispersion device for 30-60 minutes to evenly disperse the nano-particles to prepare a special wetting agent.

3. The preparation method according to claim 1, characterized in that: In step S5, the coating amount of the special sizing agent is 0.5%-1.5% of the mass of the quartz glass fiber.

4. The preparation method according to claim 1, characterized in that: The aperture accuracy of the platinum-rhodium alloy leak plate is controlled within ±0.05 μm.

5. The preparation method according to claim 1, characterized in that: The speed of drawing the quartz glass fiber is 1000-1500 m / min.

6. The preparation method according to claim 2, characterized in that: In step S41, the mass fraction of the silane coupling agent in the base solution is 13%-15%, the mass fraction of the lubricant in the base solution is 2%-7%, the mass fraction of the antistatic agent in the base solution is 2%-7%, and the mass fraction of deionized water in the base solution is 71%-83%.

7. The preparation method according to claim 2, characterized in that: In step S42, the particle size of the nano-scale titanium dioxide particles is 20-50 nm.

8. The preparation method according to claim 2, characterized in that: The mass fraction of the nano-scale titanium dioxide particles in the special impregnating agent is 3%-8%.

9. The preparation method according to claim 1, characterized in that: The temperature of the high temperature sintering treatment is 800° C.-1000° C., and the treatment time is 30-60 minutes.

10. An electronic grade quartz glass fiber cloth, characterized in that: The electronic grade quartz glass fiber cloth is prepared by the preparation method of any one of claims 1 to 9, comprising: The fiber structure is formed by weaving quartz glass fibers with a diameter of 3-9μm. The quartz glass fibers are first bundled, then wound, arranged, and twisted, and finally woven into a cloth-like structure with a specific warp and weft density ranging from 30×30 strands / cm² to 40×40 strands / cm². Wetting agent coating: A special wetting agent is coated on the fiber structure surface of the electronic grade quartz glass fiber cloth. The special wetting agent consists of a basic solution and nano-scale titanium dioxide particles. The basic solution is prepared by dissolving silane coupling agent, lubricant and antistatic agent in deionized water according to the mass ratio. The mass fraction of silane coupling agent in the basic solution is 13% -15%, the mass fraction of lubricant in the basic solution is 2% - 7%, the mass fraction of antistatic agent in the basic solution is 2% - 7%, the mass fraction of deionized water in the basic solution is 71% - 83%, the particle size of nano-scale titanium dioxide particles is 20 - 50nm, and the mass fraction in the special wetting agent is 3% - 8%, and the nano-scale titanium dioxide particles are uniformly dispersed in the basic solution by ultrasonic dispersion for 30 - 60min. The coating amount of the special wetting agent is 0.5% - 1.5% of the mass of the quartz glass fiber.

Citation Information

Patent Citations

  • Glass cloth

    JP2024150218A

Cited By

  • Quartz glass fiber cloth and preparation method thereof

    CN120818934A